1981
DOI: 10.1029/ja086ia05p03470
|View full text |Cite
|
Sign up to set email alerts
|

Inference of the ring current ion composition by means of charge exchange decay

Abstract: The analysis of data from the Explorer 45 (S³‐A) electrostatic analyzer in the energy range 5–30 keV has provided some new results on the ring current ion composition. It has been well established that the storm time ring current has a decay time of several days, during which the particle fluxes decrease nearly monotonically. In the past, ring current studies have assumed or stated that hydrogen was the dominant ion in the earth's ring current. By analyzing the measured ion fluxes during the several day storm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…On the other hand, the lower energy protons also decay much faster than those of higher energies. This is consistent with previous studies on the charge exchange lifetimes of ions with different energies [Smith and Bewtra, 1978;Smith et al, 1981], which showed that the charge exchange lifetime of protons increases with proton for energies >~10 keV, although the original studies only focused on energies up to~100 keV.…”
Section: 1002/2015ja021533supporting
confidence: 81%
“…On the other hand, the lower energy protons also decay much faster than those of higher energies. This is consistent with previous studies on the charge exchange lifetimes of ions with different energies [Smith and Bewtra, 1978;Smith et al, 1981], which showed that the charge exchange lifetime of protons increases with proton for energies >~10 keV, although the original studies only focused on energies up to~100 keV.…”
Section: 1002/2015ja021533supporting
confidence: 81%
“…The difference in the values of z during the main and recovery phases of magnetic storms is due to the prevailing mechanisms of ring-current decay, namely, the interaction with hydromagnetic waves during injections (Cornwall et al, 1970;Bespalov et al, 1989) and the charge exchange with the geocoronal hydrogen during recovery phase (Smith and Bewtra, 1978).…”
Section: The Results Of Modelling the Hourly Mean Values Of The Stormmentioning
confidence: 98%
“…Calculating the pitch-angle diffusion of ions in resonance with ion-cyclotron waves has shown that the resonance ion lifetime is a few hours. The ion-wave interactions seem to define the r value during the storm main phase, but must be allowed for also during the recovery phase when the processes of energetic ion charge exchange with neutral hydrogen constitute the principal mechanism of ion loss from ring current (Smith and Bewtra, 1978). The position of the region of the most intensive wave-particle interactions changes throughout a storm.…”
Section: Dr(t)mentioning
confidence: 98%
See 1 more Smart Citation
“…An accepted explanation is that there are losses along the drift paths. The main loss mechanism for energetic (keV) ions is charge exchange with the neutral hydrogen geocorona [ Lyons and Evans , ; Tinsley , ; Smith and Bewtra , ; Smith et al ., ; Fok et al ., ; Sheldon and Hamilton , ; Noël , ]. Kistler et al .…”
Section: Introductionmentioning
confidence: 99%